Kajian Konversi Potensi Sampah Kota Pontianak Menjadi Energi Listrik Dengan Gasifikasi Plasma - syah, Usmadian (Faculty of Engineering, Universitas Tanjungpura, 2017)
Abstract– The economic and population growth are two things that are consistent with the development of a city. Along with the process, it will arise a new problems. Waste generation has increased every year cause of environmental pollution. One of renewable energy technology that can reduse environmental pollution uses waste as raw material is PLTSa with plasma gasification. In the process of plasma gasification, the waste run into the reactor gasifier will be completely destroyed and produce residues that have economic value and synthetic gas that can be used as fuel of electricity generation plant. In this journal has been analyzed the potential of waste Pontianak city that can be converted into electrical energy. The results obtained are for 1(one) ton of waste can produce 787,5371 kWh electrical energy. From the data obtained for 6 years with the amount of waste as much as 1,378,269.20 tons can generate electrical energy of 1,085,438.10 MWh and estimation sales revenue can be obtained for Rp. 1.622.729.961.326,79. With a 12% interest rate, the production cost of the plant is Rp. 1.417.16/kWh. PLTSa with plasma gasification is one of the most effective and environmentally friendly technologies as a solution in handling waste and electrical energy crisis. Keywords- Electical Energy, Plasma Gasification, Waste, Synthetic Gas